Screening of non- Saccharomyces cerevisiae strains for tolerance to formic acid in bioethanol fermentation - Oshoma, Cyprian E.; Greetham, Darren; Louis, Edward J.; Smart, Katherine A.; Phister, Trevor G.; Powell, Chris; Du, Chenyu (Public Library of Science, 2015)
Formic acid is one of the major inhibitory compounds present in hydrolysates derived from lignocellulosic materials, the presence of which can significantly hamper the efficiency of converting available sugars into bioethanol. This study investigated the potential for screening formic acid tolerance in non-Saccharomyces cerevisiae yeast strains, which could be used for the development of advanced generation bioethanol processes. Spot plate and phenotypic microarray methods were used to screen the formic acid tolerance of 7 non-Saccharomyces cerevisiae yeasts. S. kudriavzeii IFO1802 and S. arboricolus 2.3319 displayed a higher formic acid tolerance when compared to other strains in the study. Strain S. arboricolus 2.3319 was selected for further investigation due to its genetic variability among the Saccharomyces species as related to Saccharomyces cerevisiae and availability of two sibling strains: S. arboricolus 2.3317 and 2.3318 in the lab. The tolerance of S. arboricolus strains (2.3317, 2.3318 and 2.3319) to formic acid was further investigated by lab-scale fermentation analysis, and compared with S. cerevisiae NCYC2592. S. arboricolus 2.3319 demonstrated improved formic acid tolerance and a similar bioethanol synthesis capacity to S. cerevisiae NCYC2592, while S. arboricolus 2.3317 and 2.3318 exhibited an overall inferior performance. Metabolite analysis indicated that S. arboricolus strain 2.3319 accumulated comparatively high concentrations of glycerol and glycogen, which may have contributed to its ability to tolerate high levels of formic acid.